Molecular breeding of woody plants : proceedings of the International Wood Biotechnology Symposium (IWBS) held in Narita, Chiba, Japan, March 14-17, 2001 /: proceedings of the International Wood Biotechnology Symposium (IWBS) held in Narita, Chiba, Japan, March 14-17, 2001. (2001) - Unknown
No abstract available